(untitled) (Docentes 2.0 Journal, 2024)
In Higher Education Design, when planning the Didactic Units of each subject, teachers usually include the bases and requirements of a contest. In addition to carrying out an evaluable exercise, students can participate as designers from their student stage, thus promoting their inclusion in the labor market. The research’s objective was to create an artistic production that combines the participation of students with their teachers, gathering 101 reflections on our studies and, consequently, leads to academic improvement. The research is based on the hermeneutic method, pragmatic paradigm, mixed approach, dialectical design, and multifaceted type. The research population is made up of the educational community of the art school. The instruments for collecting information have been interviews and questionnaires prepared by the students. The critical analysis of the results has been developed as a lucrative debate in the classroom, with the final result reflected in a physical and digital creation to be disseminated to other centers. In short, the research ends with a useful resource that can serve as a reference for other similar art centers.